Mayflies of the Caucasus Mountains. II. Description of the first representative of the subgenus Helvetoraeticus Bauernfeind & Soldán, 2012 (Heptageniidae: Ecdyonurus) - Kluge, Nikita J.; Godunko, Roman J.; Apanaskevich, Dmitry A. (Zootaxa, 2013)
The first representative of the subgenus Helvetoraeticus Bauernfeind & Soldán, 2012, from the Caucasus Mountains, Ecdyonurus (Helvetoraeticus) adjaricus sp. nov., is described on the basis of larvae, female imago (reared from larva) and male imago from the Autonomous Republic of Adjara, Georgia. The male imago of the new species can be separated from other representatives of Helvetoraeticus by its conspicuous yellowish wings coloration (especially of hind wings) and the shape of the penis lobes. The larva has a distinctive broad and apically pointed lateral projection on the pronotum, pointed bristles on the ventral side of the posterior border of the femora and markedly long, sharp posterolateral expansions of abdominal sterna. This last character is unique within Helvetoraeticus. The new species is most closely related to E. krueperi (Stein, 1863).